Intangible capital: The key to growth in Europe - Hannu Piekkola (Intereconomics, 2011)
Intangibles and especially organisational capital are an important source of capital deepening in European countries, albeit with significant cross-country differences. The GDP in the EU27 area is 5.5% higher if certain categories of expenditure, which have until now been considered as current costs, are classified as investments in intangibles. Intangible capital investment markedly improves the profitability of companies, given the productivity-wage gap, and leads to increasing returns in intangible capital intensive countries.
Keywords: 330